2016
DOI: 10.1097/ico.0000000000000684
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Corneal Biomechanical Properties After Descemet Stripping Automated Endothelial Keratoplasty for Pseudophakic Bullous Keratopathy

Abstract: Corneal biomechanical parameters were significantly lower in PBK eyes than in the normal fellow eyes. These metrics significantly increased after DSAEK and reached values measured in the normal fellow eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…[37] However, we recently demonstrated that corneal biomechanical parameters were significantly increased after DSAEK, attaining the values measured in normal eyes. [38] Improvement in the corneal biomechanics of the host-graft complex after DSAEK could be more prominent when a thicker graft is transplanted, which would explain the significant association between graft thickness and postoperative IOP observed in the current study.…”
Section: Discussionmentioning
confidence: 83%
“…[37] However, we recently demonstrated that corneal biomechanical parameters were significantly increased after DSAEK, attaining the values measured in normal eyes. [38] Improvement in the corneal biomechanics of the host-graft complex after DSAEK could be more prominent when a thicker graft is transplanted, which would explain the significant association between graft thickness and postoperative IOP observed in the current study.…”
Section: Discussionmentioning
confidence: 83%